Seeing beyond design: exploring non-engineering functions of technology in engineering ethics - Hoeffner, Jacob, author; Rollin, Bernard, advisor; Hamid, Idris, committee member; Didier, John, committee member (Colorado State University. Libraries, 2020)
The purpose of this paper is to draw a distinction between the function of technology in engineering contexts and non-engineering contexts. The first two sections identify and elaborate this distinction; the final portion of the paper demonstrates why engineers should be aware of non-engineering functions of technology in light of this distinction. Both engineering (or design-based) and non-engineering evaluations of technology can be categorized within the genus of engineering ethics. However, I do not intend to provide a commentary on how engineers might improve the design process. Rather, my goal is to provide an argument as to why it is important for engineers to understand the limitations of the design method of evaluation. In order to do so, I will outline various non-engineering evaluations of conventional nuclear technology and the correlations between non-engineering evaluations and advanced nuclear designs of today. In closing, I will distinguish engineering as a method, a metaphysical concept, from engineering as a profession, an ethical concept. I will conclude by demonstrating that understanding the limitations of the design method is an essential feature of professional engineering. Through introducing the limitations of the design method it will be clear why engineers should learn to see beyond the design.
Keywords: engineering ethics; engineering education; philosophy of technology